Seletividade de formulações de clomazone aplicado em pré e pós emergência no desenvolvimento inicial do pinhão-manso - Berté, Luiz Neri (2013)
Due to the expansion of the cultivation of Jatropha curcas, in Brazil studies are needed covering agronomic management, especially in weed management, due to the susceptibility of Jatropha curcas the competition and lack of information. Thus, the objective was to quantify the effects of increasing doses of clomazone in the initial development of the Jatropha curcas to identify selective herbicide doses for culture. To this end, two experiments were conducted in the randomized factorial 2 x 5 in randomized blocks with 4 replications. The first factor representing the combination of two formulations of the herbicide clomazone being used CS (suspension of encapsulated) formulations and EC (emulsifiable concentrate) the commercial product GAMIT and 360 CS ® 500 EC ® and five dosages 0; 250; 500; 1000 and 2000 g ha-1. In the first experiment we studied the application of clomazone reemergence and second applying post-emergence. To identify the effects of clomazone on culture biometric, physiological and biochemical parameters were investigated. In trials of pre and post emergence, application of clomazone herbicide symptoms caused the higher dosages used, as evidenced by symptoms of leaf chlorosis. In both trials and for all doses and formulations used, plant height and stem diameter showed a linear increase during the trial period. In pre emergence, application of clomazone hindered the development of biometric parameters, however, the post emergence test the changes were less dramatic. The biochemical and physiological parameters were affected by the application of clomazone in pre and post emergence. The application of clomazone in pre and post-emergence in the culture of Jatropha, the suspension formulations of encapsulated (GAMIT 360 CS ®) and emulsifiable concentrate (EC GAMIT 500 ®) to a dose of 2000 g ha-1 produced an intermediate symptoms phytointoxication and negatively affect early development and dry matter accumulation by plants. The recovery of plants after 51 days when applied before emergence, and 42 days in the post application emergency suggest the existence of clomazone selectivity for this crop in both formulations until the dose of 500 g ha-1. However, further studies needed for longer duration and are contemplating the crop to verify the negative effects of the herbicide in the production of jatropha aspects